Clinical presentation and management of atypical polypoid adenomyomas: Systematic review of the literature. (May 2019) - Mikos, Themistoklis; Tsolakidis, Dimitrios; Grimbizis, Grigoris F.
Abstract: The aim of this study is to investigate clinical behavior of Atypical Polypoid Adenomyomas (APAs) and to describe the rates of (i) recurrences, (ii) their association with endometrial hyperplasia and (iii) with endometrial cancer. All studies that reported the outcome of the clinical management of patients with histologically proven APAs were included. A review of the English literature since 1970 was systematically performed (PROSPERO No CRD42018080003). A quality assessment tool was used to assess the scientific value of all the studies. Main contribution of this review is the proposal of new definitions regarding the clinical behaviour of APAs: Cure, Residual or persistent APA, Recurrent APA, Synchronous endometrial hypeprasia, Subsequent endometrial hyperplasia, Synchronous endometrial cancer, and Subsequent endometrial cancer, are terms elucidated in the context of this review. Their rates after initial diagnosis and treatment of APAs are presented as the main outcome measures. 63 studies and 350 patients were included in the systematic review. Fifteen studies that reported 208 patients who did not have hysterectomy as initial treatment were included for further quantitative assessment. The cure rate of APAs in cases where uterus was preserved was 51.0% (106/208), the residual rate of APA was 20.2% (42/208), the recurrence rate of APA was 35.1% (73/208), the concurrent endometrial hyperplasia rate was 7.2% (15/208), the concurrent endometrial cancer rate was 4.8% (10/208), the subsequent endometrial hyperplasia rate of was 6.7% (14/208), and the subsequent endometrial cancer rate of was 10.1% (21/208). Moreover, 56.4% of the patients with APA who opted for uterine sparing treatment and wished to conceive they had a viable pregnancy. The use of hysteroscopic techniques at the initial management of APAs is related with significantly decreased residual rate, and signicantly increased cure rates. In this review, the recurrence rate and the association of APAs with cancer appeared to be higher compared to the previously reported in the literature rates. APAs comprise an intriguing clinical entity that needs individualized treatment, considering the increased association to serious gynecological diseases. Hysterectomy is the appropriate treatment, however uterus-sparing surgery can be offered to selected patients.